Strategi Kesopanan dalam Tuturan Permintaan: Suatu Studi Kasus pada Mahasiswa Jurusan Sastra Inggris FIB UGM - , ALI IQBAL ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This paper examines the politeness strategies in making request, with a case study of English Department Students of Faculty of Cultural Sciences UGM. The purpose of this research is to identify the politeness strategies used in making request and to discover whether the politeness strategies can be affected by variation of hearers. This research uses open questionnaire in the form of DCT (Discourse Completion Test) as the method to collect the data. There are three scenarios in the DCT in which the 30 research participants have to act in response in the form of writing. There are total of 90 request utterances collected in this research. The results show the uses of certain politeness strategies in making request in accordance with the politeness theory outlined by Brown and Levinson. Moreover, this result might produce a degree (assumption) to predict the common politeness strategies used by the English Department Students of Universitas Gadjah Mada.